The Implementation of students' moral literacy through Pancasila values in the implementation of teaching campuses in Samarinda City - Majid, Novita; Wingkolatin, Wingkolatin; Rachmad, Edi; Riayanti, Rini (Educational Studies: Conference Series, 2023)
The profile of Pancasila students is part of the Ministry of Education and Culture's vision and mission, which is very important to be implemented in educational institutions, to grow and develop students as Pancasila students, who demonstrate the value of faith, fear of God Almighty and have noble character, critical thinking, global diversity, mutual cooperation, independent and creative. Under these conditions the moral literacy movement through Pancasila values in the implementation of teaching campuses as an effort to strengthen character is very important to be reapplied to Indonesian society, especially youth and students. This research focuses on implementing Pancasila values in SDN Kota Samarinda. students through Pancasila values in the implementation of teaching campuses as an effort to strengthen character in Samarinda City Elementary School. This study aims to analyze and describe moral literacy, Pancasila values in the implementation of teaching campuses and their implications for SDN Kota Samarinda students. In this research technique in the form of case studies using a qualitative approach. Data collection techniques were carried out by interviews, documentation, observation. Data analysis used Miles and Hubermen's model analysis, including data reduction, data interpretation or data collection, presentation, data verification and drawing conclusions.